Load Management Strategy as an Effort to Prevent Overuse Injuries in Athletes of the Redjay Bekasi Basketball Club (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Overuse injuries are one of the most common problems in competitive sports, particularly in basketball, which is characterized by repetitive and intense movements. This study aims to evaluate the effectiveness of load management strategies in preventing overuse injuries in athletes from the Redjay Bekasi Basketball Club. The research method used was quantitative with an observational analytical design and a correlational study approach. Internal loads were monitored using the session-RPE (s-RPE) method for six weeks, while overuse injury incidence was recorded through weekly injury surveillance. Spearman correlation analysis and logistic regression were used to examine the relationship between training load and injury risk. The results showed that weekly load spikes of more than 15–30% were significantly associated with an increased incidence of overuse injuries in the following week. Conversely, stable chronic loads appeared to have a protective effect against injury. These findings support the importance of structured load management as an injury prevention strategy. This study was limited by its sample size and relatively short monitoring duration. Further research is recommended to include external load monitoring and a longer observation period.